The Course of Commodity Prices - Crum, W. L. (The Review of Economics and Statistics, 1934)
IN addition to their customary significance for the interpretation of economic conditions, commodity prices have at present a peculiar importance because of the emphasis placed upon them in the discussion of official attempts to stimulate recovery. During the formulation and operation of the recovery program, great emphasis has been laid upon the supposed necessity of inducing an advance in prices. Destructive price cutting was listed as a chief form of excessive competition, and stable or advancing prices were regarded as necessary in order to bring to an end the wave of liquidation. The advance of particular types of wholesale prices, especially those of agricultural and some other basic commodities, was accepted as a means of achieving at least in part that redistribution of wealth (income) which was one of the announced objectives of official policy. Officialdom did not overlook, moreover, that advancing prices are generally considered a symbol of improving business, and would therefore have a favorable psychological effect. Various items of official policy accordingly had the elevation of prices as an important, if not their main, objective. These policies appeared not merely in'the handling of the money problem, with the actual devaluation of the dollar and the continuing threat of inflation, but also in numerous phases of the attempted control of agriculture and other industries. The systematic purpose to raise prices was so frankly and clearly indicated in the so-called recovery legislation, in the related administrative regulations, and in the frequent and emphatic official pronouncements, that it seems almost unnecessary to recall the facts. Through it all the official mind 'clearly supposed -or wished to be thought to suppose that there existed somewhere between producer and consumer a great slack which could be taken up, so that the advance of prices received by producers need not be transmitted in full and in all cases into an equivalent advance of prices paid by consumers. Allegedly excessive increases in prices to consumers were frowned upon, and somewhat energetic measures were taken to prevent or discourage such increases. It was a no time officially' promised, however, that consumers would not be called upon to foot a large portion of the bill for recovery ultimately, if not immediately.